Ferroptosis in Parkinson’s disease: glia–neuron crosstalk - Wang, Zhang-Li; Yuan, Lin; Li, Wen; Li, Jia-Yi (Trends in molecular medicine, 2022)
Parkinson’s disease (PD) is characterized by dopaminergic (DA) neuron loss and the formation of cytoplasmic protein inclusions. Although the exact pathogenesis of PD is unknown, iron dyshomeostasis has been proposed as a potential contributing factor. Emerging evidence suggests that glial cell activation plays a pivotal role in ferroptosis and subsequent neurodegeneration. We review the association between iron deposition, glial activation, and neuronal death, and discuss whether and how ferroptosis affects α-synuclein aggregation and DA neuron loss. We examine the possible roles of different types of glia in mediating ferroptosis in neurons. Lastly, we review current PD clinical trials targeting iron homeostasis. Although clinical trials are already evaluating ferroptosis modulation in PD, much remains unknown about metal ion metabolism and regulation in PD pathogenesis. Iron uptake, storage, efflux, and utilization are essential for maintaining iron homeostasis. Abnormal expression of proteins involved in these processes related to iron homeostasis may cause iron overload and induce subsequent ferroptosis, which is associated with the pathogenesis of neurodegenerative disease.Crosstalk between glia and neurons underlies the ferroptotic alterations in DA neurons and form a vicious circle in promoting PD pathogenesis.Possible mechanisms of iron transfer between glia and neurons include exosomes and tunneling nanotubes. They may determine the efficacy of ferroptosis inhibitors and provide a clue for exploring novel therapeutic interventions for PD.Joint medications with ferroptosis inhibitors and anti-inflammatory medicines may provide a potential strategy for the treatment of PD and related neurodegenerative diseases.